2009
DOI: 10.1002/jcu.20585
|View full text |Cite
|
Sign up to set email alerts
|

Association of atherosclerotic risk factors with carotid adventitial thickness assessed by ultrasonography

Abstract: The association between IMT and AT may reflect an interaction between intimal, medial, and adventitial pathology. Different risk factors are associated with the increased AT or IMT. It is possible that inflammation and some chronic infections, such as those induced by C. pneumoniae, could have a marked influence on adventitial cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Seven subjects in this group were current smokers. The AS group consisted of 36 subjects (17 women, 19 men), aged 53 ± 8 years (age range, 40–60 years), including 3 subjects with hyperlipidemia, 11 with hypertension, 6 with diabetes mellitus (defined as a fasting glucose level ≥7.0 mmol/l or taking antidiabetic medication 14), 7 with both hypertension and diabetes mellitus, 3 with cerebrovascular disease, and 6 with coronary heart disease. All patients in the group were receiving, or had received, lipid‐lowering intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven subjects in this group were current smokers. The AS group consisted of 36 subjects (17 women, 19 men), aged 53 ± 8 years (age range, 40–60 years), including 3 subjects with hyperlipidemia, 11 with hypertension, 6 with diabetes mellitus (defined as a fasting glucose level ≥7.0 mmol/l or taking antidiabetic medication 14), 7 with both hypertension and diabetes mellitus, 3 with cerebrovascular disease, and 6 with coronary heart disease. All patients in the group were receiving, or had received, lipid‐lowering intervention.…”
Section: Resultsmentioning
confidence: 99%
“…IMT was defined as the distance between the lumen‐intima interface and the media‐adventitia interface, as reported previously. 8, 14 A longitudinal region of interest was chosen (Figure 1A), and the intima‐media boundaries were demarcated (Figure 1B and 1C). Measurement was performed along each vertical pixel line along the entire target vessel in the longitudinal section.…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies have indicated that the spatial resolution used in the current protocol is suffi-cient to image the adventitia, 20,21 especially in the diseased segment, improvements in temporal resolution will enable more accurate estimation of perfusion parameters by capturing contrast kinetics in more detail. Alternatively, contrast agents with larger molecular weight and, thus, slower kinetics can be helpful for adventitial perfusion imaging.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Indeed, previous studies using MRI have shown enhancement of the adventitia after contrast injection. 2224 Furthermore, the feasibility of applying dynamic contrast-enhanced MRI (DCE-MRI) with kinetic modeling to study adventitial perfusion has been shown, which generates physiological parameters of VV.…”
mentioning
confidence: 99%
“…The middle cerebral artery is a straight blood vessel with rare congenital variation and could be used to predict the risk of cerebral vascular disease induced by atherosclerosis. PI is an index reflecting cerebral vascular compliance and elasticity, while RI describes cerebral vascular resistance, both of which could be used as sensitive indexes for the diagnosis and prognosis of ischemic cerebrovascular disease [36]. In this study, Vs/Vd, PI, and RI in the intensive management group were significantly lower compared with the control group, indicating that intensive treatment can alleviate cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 64%